Need to factor this trinomial, and not having much luck.

6m

^{2}-5m-4.Try to break the second term into two. Let us try to present 5m as 2m+3m.

6m

^{2}-3m-2m-4. Now let us group terms together.(6m

^{2}-3m)-(2m+4) Factor out common factors.3m(2m-1)-2(m+2). There is no way to factor further. Let us try different grouping.

(6m

^{2}-2m)-(3m+4)=2m(3m-1)-(3m+4) Again, no luck.Let us try this:

6m

^{2}-5m-4=6m^{2}-8m+3m-4=(6m^{2}-8m)+(3m-4)=2m(3m-4)+(3m-4). Now we got a common factor at last!Factor (3m-4) out to obtain:

**6m**

^{2}-5m-4=(3m-4)(2m+1)